Analisis Penentuan Harga Pokok Produksi Dalam Menentukan Harga Jual Dengan Menggunakan Metode Full Costing Dan Variable Costing Pada UMKM “Kitchen Meals” - Monika Handayani; Anugrah Wati Indah Sahrul (Indonesian Journal of Applied Accounting and Finance, 2024)
This research delves into effective financial management strategies for students engaged in multitasking, working while studying, and managing Micro, Small, and Medium Enterprises (MSMEs). A qualitative approach with a case study design is employed, integrating experience, relationships, and discipline in understanding financial management strategies. The research findings indicate that personal experience plays a crucial role in building a strong foundation for financial strategies. Well-established networks, particularly with customers and fellow entrepreneurs, prove to be vital support for business growth. Additionally, discipline in recording and managing finances emerges as a key factor in achieving long-term financial goals